2014
DOI: 10.5120/14852-3218
|View full text |Cite
|
Sign up to set email alerts
|

Bank Direct Marketing Analysis of Data Mining Techniques

Abstract: All bank marketing campaigns are dependent on customers' huge electronic data. The size of these data sources is impossible for a human analyst to come up with interesting information that will help in the decision-making process. Data mining models are completely helping in the performance of these campaigns. This paper introduces analysis and applications of the most important techniques in data mining; multilayer perception neural network (MLPNN), tree augmented Naïve Bayes (TAN) known as Bayesian networks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 15 publications
0
28
0
5
Order By: Relevance
“…To estimate the parameters (means and variances of the variables) necessary for classification, the classifier requires only a small amount of training data. It also handles real and discrete data [22].…”
Section: A Logistic Regressionmentioning
confidence: 99%
“…To estimate the parameters (means and variances of the variables) necessary for classification, the classifier requires only a small amount of training data. It also handles real and discrete data [22].…”
Section: A Logistic Regressionmentioning
confidence: 99%
“…Repository. This dataset are collected and arranged by [33] and also utilized by [34]. Our proposed hybrid approach used this dataset to determine its performances and resolves the privacy issues.…”
Section: Data Collection Procedures and Publishing On Cloudmentioning
confidence: 99%
“…In another piece of research, Elsalamony [32] focused on increasing the effectiveness of the marketing campaign by finding the major attributes that affected the success of the phone call. The author compared three classification methods: multilayer perception neural network (MLPNN), Bayesian networks, logistic regression (LR), and C5.0 on the direct marketing dataset and found that C5.0 gave the best results, with the testing part scoring:…”
Section: Comparison With Other Techniquesmentioning
confidence: 99%